The influence of E-WOM and brand image on purchase decision of the originote - Adinda, Gadis Tri; Purmono, Bintoro Bagus; Afifah, Nur; Barkah, Barkah; Marumpe, Dody Pratama (Jurnal Ekonomi, 2024)
This study explores the increasing popularity of social media, particularly the TikTok platform, in influencing changes in online shopping behavior. The primary focus is to examine the impact of Electronic Word of Mouth (E-WOM) and brand image on purchase decisions, with consumer trust as a mediating variable. The research design adopts a quantitative approach with a descriptive method. Data is collected through surveys, targeting all TikTok app users who have made purchases of The Originote skincare products, totaling 223 respondents. Non-probability sampling, specifically purposive sampling, is employed. Data is analyzed using Structural Equation Modeling (SEM) and the statistical tool AMOS. This method strengthens hypotheses, tests and evaluates relationships between the independent factors of E-WOM and brand image, the dependent variable of purchase decisions, and the mediating role of consumer trust. The aim of this research is to provide insights into the influence of E-WOM and brand image on purchase decisions, with consumer trust serving as the mediator. The findings are expected to contribute to a better understanding of online shopping in the era of social media, particularly on the TikTok platform.